Facilities for Centralized Isolation and Quarantine for the Observation and Treatment of Patients with COVID-19. (July 2021) - Wang, Xianliang; Wang, Jiao; Shen, Jin; Ji, John S.; Pan, Lijun; Liu, Hang; Zhao, Kangfeng; Li, Li; Ying, Bo; Fan, Lin; Zhang, Liubo; Wang, Lin; et al.
Abstract: The coronavirus disease 2019 (COVID-19) pandemic increased the burden on many healthcare systems and in the process, exposed the need for medical resources and physical space. While few studies discussed the efficient utilization of medical resources and physical space so far. Therefore, this study aimed to summarize experiences related to facilities used for centralized isolation for medical observation and treatment during the COVID-19 pandemic in China and to provide suggestions to further improve the management of confirmed cases, suspected cases, and close contacts. In China, three types of facilities for centralized isolation (Fangcang shelter hospitals, refitted non-designated hospitals, and quarantine hotels) underwent retrofitting for the treatment and isolation of confirmed and suspected cases. These facilities mitigated the immediate high demand for space. Moreover, in order to minimize infection risks in these facilities, regulators and governmental agencies implemented new designs, management measures, and precautionary measures to minimize infection risk. Other countries and regions could refer to China's experience in optimally allocating social resources in response to the COVID-19 pandemic. As a conclusion, government should allocate social resources and construct centralized isolation and quarantine facilities for an emergency response, health authorities should issue regulations for centralized isolation facilities and pay strict attention to the daily management of these facilities, a multidisciplinary administration team is required to support the daily operation of a centralized isolation facility, in-depth studies and international collaboration on the centralized isolation policy are encouraged.